Echocardiographic Assessment of the Pulmonary Venous Flow: An Indicator of Increased Pulmonary Flow in Congenital Cardiac Malformations - Rivera,Ivan Romero (2002)
OBJECTIVE: To identify the left inferior pulmonary vein as an indirect marker of increased pulmonary flow in congenital heart diseases.METHODS: We carried out a prospective consecutive study on 40 patients divided into 2 groups as follows: G1 - 20 patients diagnosed with congenital heart disease and increased pulmonary flow; G2 (control group) - 20 patients who were either healthy or had congenital heart disease with decreased or normal pulmonary flow. We obtained the velocity-time integral of the left inferior pulmonary vein flow, excluding the "reverse A" wave, with pulsed Doppler echocardiography.RESULTS: In G1, 19 out of the 20 patients had well-identified dilation of the left inferior pulmonary vein. No G2 patient had dilation of the left inferior pulmonary vein. Dilation of the left inferior pulmonary vein in conditions of increased pulmonary flow had sensitivity of 95%, specificity of 100%, positive predictive value of 100%, and negative predictive value of 95% (1 false-negative case). The integral of time and velocity of the pulmonary venous flow obtained with pulsed Doppler echocardiography was greater in the G1 patients (G1=25.0±4.6 cm versus G2=14.8±2.1 cm, p=0.0001).CONCLUSION: The identification of dilation of the left inferior pulmonary vein suggests the presence of congenital heart disease with increased pulmonary flow. This may be used as an indirect sign of increased flow, mainly in malformations of difficult diagnosis, such as atrial septal defects of the venous sinus or coronary sinus type.